Clinical pearls: Laboratory assessments of direct oral anticoagulants (DOACS) - Gosselin, Robert C.; Douxfils, Jonathan; Adcock, Dorothy (Hämostaseologie, 2017)
Direct oral anticoagulants (DOACS) are being used for stroke prevention in patients with atrial fibrillation as well as for prophylaxis and treatment of venous thromboembolism. Clinicians who treat, or may encounter, patients with DOAC exposure, should be aware of the limitations of coagulation testing in this setting, and seek counsel from their laboratory to understand the effects of DOACS on coagulation results. Generally, assays that employ clot based principles, or methods that require thrombin or Factor Xa activation or substrates may be affected by the presence of DOACS. The clinical laboratory should have an algorithmic testing plan for adequately assessing the presence of all DOACS and readily provide this information to clinicians. We describe Clinical Pearls for DOAC assessment using common and esoteric coagulation testing.
Keywords: Dabigatran; rivaroxaban; apixaban; edoxaban; direct oral anticoagulants